Substation reliability and its impacts on composite system adequacy - Ren, Shuhua (2008)
Modern society expects the production and distribution of electric power to be accomplished at maximum reliability and minimum cost. Reliability and reliability worth assessment plays an important role in power system planning, operation, and expansion. Substation and switching station, which forms a link between the bulk transmission system and the generation system, is the pivotal portion of an electric power system. Failure events in substations and switching stations often result in multiple outages of generators, lines, and/or loads in power system. Station-originated outages are normally of short duration but their effect on the security and stability of power systems may be quite severe. The reliability evaluation of station-originated outages is therefore of vital importance. How to provide the system planners and operators necessary reliability indices and reliability worth information about station-originated outages is a challenging task which was undertaken in this project.